THE LINGUISTIC ANALYSIS OF THE FAIRY TALE - Goloshumova, A.A. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
А fairy tale is an imaginary story that may feature folkloric characters (such as fairies, goblins, elves, trolls, witches, giants, and talking animals) and magic, often involving a sequence of event s. The concept is also used to describe as unusual happiness, as in "fairy tale ending" (a happy ending) or "fairy tale romance," though not all fairy tales have a happy end. Fairy tales are a genre of literature. They have their roots in the oral tradition. Fairy tales with very similar story, characters, and figures are found spread across many different cultures. A fairy tale is a wonderful work of art, familiar to each of us from childhood. There are various translations of the tale. Some scientists say that a fairy tale is an absolute fiction, which is independent of reality. But the most precise definition of a fairy tale is a story, often intended for children, that features fanciful and wondrous characters such as elves, goblins, wizards, and even, but not necessarily, fairies. The term “fairy” tale seems to refer more to the fantastic and magical setting or magical influences within a story, rather than the presence of the character of a fairy within that story. Fairy tales are often traditional; many were passed down from story-teller to story-teller before being recorded in books. Vocabulary is a central component of language teaching and is of great significance to language learners. Words are the building blocks of a language since they label objects, actions, and ideas without which people cannot convey the intended meaning.
Keywords: introduction; fairy tale; linguistic feature; compositional feature; semantic feature; text; literature; meaning; study of linguistics; folklore; magic